Undergraduates' perceptions of visual characteristics and safety of urban parks' naturalistic landscapes in The Klang Valley, Malaysia - Farbod, Sara (2013)
Human activities, including urbanization, continue to result in species extinction and threatening the biodiversity on which life depends. This prompted landscape architects to focus on creating more urban parks that are naturalistic. This could help to enhance biodiversity by increasing the variety of plants and wildlife in urban areas. However,some studies have cautioned that urban public may consider naturalistic landscapes to be unsafe and perceived safety influence urbanites willingness to use parks. Previous studies have shown the influence of visual characteristics on perceived safety. However,there is a dearth of systematic studies on the relationship between landscape visual characteristics and perceived safety of naturalistic landscapes in urban parks. This study aimed to fill in this gap through the following objectives: 1) To examine public perceptions of safety; 2) To determine perceived safety according to visual characteristics; and 3) To determine the factors that influence perceived safety. This study involved the selection and testing of naturalistic scenes in urban parks. The visual characteristics measured included Prospect, Refuge and Escape (each was measured by three indicators). Visual characteristics were also described verbally in the questionnaire. The study used photo-questionnaires of naturalistic landscapes in urban parks in Klang Valley, Malaysia. They were administered to 360 undergraduate students from Universiti Putra Malaysia in Serdang, Selangor. The data collected were analyzed using descriptive and inferential statistics such as Repeated Measure ANOVA,correlation and regression analysis. Results indicated that there is a significant difference between respondents’ perceived safety for different visual characteristics, even when the effect of non-visual factors (concerns about dangers, together with personal characteristics and experiences) was removed. Perceived safety for Refuge was lower than that for Prospect and Escape. The results revealed that the perceived safety for Prospect, Refuge and Escape are predictors of perceived safety for naturalistic landscapes. Significant relationship between photographs and verbal statements of measures of perceived safety confirmed the validity of the constructs.. Results also indicated violent crime and social incivilities successfully predicted perceived safety. In terms of demographic variables only ethnicity influenced the perceived safety of participants. This study showed that perceived safety is a complex issue involving several elements,both physical and social. Therefore, physical and social measures should be combined in strategies to improve safety. This information can be useful for landscape planners, designers and authorities in the design and management of naturalistic landscapes in urban parks that are perceived to be safe by users.